Chapter 6: The righteousness of industrialism? Analyzing the legacy behind 'The Present Moment' in Christian technological ethics - Kidwell, J (2010)
Several prominent moral theologians have suggested that the current environmental crisis is a consequence of disordered accounts of human work and labour. Though this has inspired abstract speculation about the modern tranformation of labour, few analyses anchor such reflection in the concrete historical experience of Christian labourers or probe for theologically construed responses in context. In this paper, I will seek to identify a framework which can better represent the complex relation between Christian moral reflection and industrialisation as it developed in the nineteenth-century by offering brief but sustained analysis of two test cases: the Luddite revolts (1811-1812) and the Great Exhibition (1851). Contrary to the narrative which holds that the industrial transformation of labour emerged while theological reflection was increasingly marginalised by secularisation, I will seek to draw attention to the presence of theological reflection in two different means of historical response, the protest and promotion of industry.